Oxidized low-density-lipoprotein accumulation is associated with liver fibrosis in experimental cholestasis (Clinics, 2008)
OBJECTIVE: The aim of the present study was to examine the probable relationship between the accumulation of oxLDL and hepatic fibrogenesis in cholestatic rats. INTRODUCTION: There is growing evidence to support the current theories on how oxidative stress that results in lipid peroxidation is involved in the pathogenesis of cholestatic liver injury and fibrogenesis. One of the major and early lipid peroxidation products, OxLDL, is thought to play complex roles in various immuno-inflammatory mechanisms. METHODS: A prolonged (21-day) experimental bile duct ligation was performed on Wistar-albino rats. Biochemical analysis of blood, histopathologic evaluation of liver, measurement of the concentration of malondialdehyde (MDA) and superoxide-dismutase (SOD) in liver tissue homogenates, and immunofluorescent staining for oxLDL in liver tissue was conducted in bile-duct ligated (n = 8) and sham-operated rats (n = 8). RESULTS: Significantly higher levels of MDA and lower concentrations of SOD were detected in jaundiced rats than in the sham-operated rats. Positive oxLDL staining was also observed in liver tissue sections of jaundiced rats. Histopathological examination demonstrated that neither fibrosis nor other indications of hepatocellular injury were found in the sham-operated group, while features of severe hepatocellular injury, particularly fibrosis, were found in jaundiced rats. CONCLUSION: Our results support the finding that either oxLDLs are produced as an intermediate agent during exacerbated oxidative stress or they otherwise contribute to the various pathomechanisms underlying the process of liver fibrosis. Whatever the mechanism, it is clear that an association exists between elevated oxLDL levels and hepatocellular injury, particularly with fibrosis. Further studies are needed to evaluate the potential effects of oxLDLs on the progression of secondary biliary cirrhosis.